Inspiratory muscle training does not improve clinical outcomes in 3-week COPD rehabilitation: results from a randomised controlled trial. Issue 1 (25th January 2018) - Schultz, Konrad; Jelusic, Danijel; Wittmann, Michael; Krämer, Benjamin; Huber, Veronika; Fuchs, Sebastian; Lehbert, Nicola; Wingart, Silke; Stojanovic, Dragan; Göhl, Oliver; Alma, Harma J.; de Jong, Corina; et al.
The value of inspiratory muscle training (IMT) in pulmonary rehabilitation in chronic obstructive pulmonary disease (COPD) is unclear. The RIMTCORE (Routine Inspiratory Muscle Training within COPD Rehabilitation) randomised controlled trial examined the effectiveness of IMT added to pulmonary rehabilitation. In total, 611 COPD patients (Global Initiative for Chronic Obstructive Lung Disease stage II–IV) received a 3-week inpatient pulmonary rehabilitation, of which 602 patients were included in the intention-to-treat analyses. The intervention group (n=300) received highly intensive IMT and the control group (n=302) received sham IMT. The primary outcome was maximal inspiratory pressure ( P Imax ). The secondary outcomes were 6-min walk distance, dyspnoea, quality of life and lung function. Outcomes were assessed pre- and post-pulmonary rehabilitation. ANCOVA was used. The intervention group showed higher effects in P Imax (p<0.001) and forced inspiratory volume in 1 s (p=0.013). All other outcomes in both study groups improved significantly, but without further between-group differences. Sex and pulmonary rehabilitation admission shortly after hospitalisation modified quality of life effects. IMT as an add-on to a 3-week pulmonary rehabilitation improves inspiratory muscle strength, but does not provide additional benefits in terms of exercise capacity, quality of life or dyspnoea. A general recommendation for COPD patients to add IMT to a 3-week pulmonary rehabilitation cannot be made. IMT added to a 3-week PR programme improved P Imax and FIV 1, but not exercise capacity, dyspnoea or QoL #COPD http://ow.ly/hPGK30gfqej